lncRNA MIAT suppression alleviates corneal angiogenesis through regulating miR-1246/ACE - Bai, Yanhui (Cell Cycle, 2019)
Corneal neovascularization (CRNV) is a prevalence eye disorder that affects the transparency and refraction properties of eyes. To explore the correlation between the level of Angiotensin II (Ang II) and corneal angiogenesis, the rat model of CRNV was established using alkali-burn, while the human umbilical vein endothelial cells (HUVECs) were stimulated using VEGF to induce the CRNV cells in vitro. RNA immunoprecipitation (RIP) and RNA pull-down were performed to validate the relationship between MIAT and miR-1246. The expression of MIAT and Ang II was increased, while miR-1246 was decreased in CRNV rat model. VEGF stimulation significantly promoted cell proliferation and migration of HUVECs, knockdown of MIAT dramatically reversed the effects of VEGF, while cells co-transfected with miR-1246 inhibitor obviously abolished the effect of VEGF+si-MIAT, however, enalaprilat abolished the effects of VEGF+si-MIAT+miR-1246 inhibitor. MIAT directly regulated the expression of miR-1246. In conclusion, VEGF stimulation promoted cell proliferation and migration of HUVECs mainly through regulating MIAT/miR-1246/ACE.